Development and commercialization of the green muscle biopesticide - Douthwaite, Boru; Langewald, J.; Harris, J. (2001)
Locusts are the most feared pests of farmers living around the world’s major deserts. Millions of liters of environmentally damaging pesticides are sprayed over vast areas of land to control them and their grasshopper cousins. This paper tells the life history of the LUBILOSA (Lutte Biologique contre les Locustes et Sauteriaux) project, set up in 1989, and the development of a biological pesticide which kills locusts and grasshoppers without harming the environment. Commercial manufacture and real adoption has begun, although the benefits have yet to pay for the US$15 million spent on the project. The project has had some major spin-offs including the development of a similar biopesticide in Australia, and the development of biopesticides to control termites. Good science alone has by no means been the only ingredient of the success so far. One crucial factor has been the willingness of donors to provide funding for the 10 years of research and development often required to turn basic research into a useful product. A second factor is the early forging of partnerships between donors, several research institutes, national agricultural research and extension systems (NARES), nongovernmental organizations (NGOs), the Food and Agriculture Organization of the United Nations (FAO), private sector companies, and farmers that has ensured that sufficient expertise was available when needed. A by- product of this collaboration is the creation of a “constituency of support” around Green Muscle® and it is this constituency which, more than anything, will determine the eventual impact and return on investment of the LUBILOSA project. This is because the eventual level of sales of Green Muscle depends on the correction of the market failure whereby the human and environmental health costs of spraying chemical pesticides are not charged to the purchaser. Policy change is required to correct this and it is in the constituency’s power to bring about this policy change. LUBILOSA project management and donors have shown themselves very aware of this reality by proposing and funding a “stewardship” phase for the project to both lobby the constituency and keep it together during the early adoption 4 phase, as well as to ensure a seamless transfer of researcher knowledge about Green Muscle to the private sector manufacturers. The need for product “stewardship” or “championing” has long been recognized in the private sector but has been absent from a research world which has attempted, until recently, to separate “upstream” basic research from “downstream” adaptive research and extension. Product championing may well be essential for creating and cementing synergies between the public and private sectors and between scientific “knowledge” and practical “know-how”.